Silent Human Trypanosoma brucei gambiense Infections around the Old Gboko Sleeping Sickness Focus in Nigeria - Karshima Solomon Ngutor; Lawal A. Idris; Okubanjo Oluseyi Oluyinka (Journal of Parasitology Research)
Trypanosoma brucei gambiense causes Gambian trypanosomosis, a disease ravaging affected rural parts of Sub-Saharan Africa. We screened 1200 human blood samples for T. b. gambiense using the card agglutination test for trypanosomosis, characterized trypanosome isolates with Trypanosoma gambiense serum glycoprotein-PCR (TgsGP-PCR), and analyzed our data using Chi square and odds ratio at 95% confidence interval for statistical association. Of the 1200 samples, the CATT revealed an overall infection rate of 1.8% which ranged between 0.0% and 3.5% across study sites. Age and sex based infection rates ranged between 1.2% and 2.3%. We isolated 7 (33.3%) trypanosomes from the 21 seropositive samples using immunosuppressed mice which were identified as T. b. gambiense group 1 by TgsGP-PCR. Based on study sites, PCR revealed an overall infection rate of 0.6% which ranged between 0.0% and 1.5%. Females and males revealed PCR based infection rates of 0.3% and 0.8%, respectively. Infection rates in adults (1.3%) and children (0.1%) varied significantly (p<0.05). We observed silent T. b. gambiense infections among residents of this focus. Risks of disease development into the second fatal stage in these patients who may also serve as reservoirs of infection in the focus exist.